Pull My Daisy. A Bebop Revolution - Sara Villa (University of Edinburgh, 2006)
On the 12th May 1959 Pull My Daisy, a film written and narrated by Jack Kerouac and directed by Alfred Leslie and Robert Frank, was first projected at the Museum of Modern Art in New York City. Even though the film was enthusiastically acclaimed by critics like Jonas Mekas as one of the most accomplished productions of the New Cinema Group, as a "free improvisation" (Mekas, "New York Letter" 19) and as a fresh, lively sketch of Beat life, nonetheless some scholars criticized the production. What the adverse reviewers did not realize, however, is that the kind of truthfulness intended by both the directors of Pull My Daisy and by Kerouac himself was utterly different from the one which distinguishes the journalistic approach, the naked camera lenses that record the events of an ordinary moment just as they happen. This essay will explore the improvised techniques and 'bebop poetics' in Pull My Daisy What the adverse reviewers did not realize, however, is that the kind of truthfulness intended by both the directors of Pull My Daisy as a free improvisation stemming from a steady basis of pre-arranged themes, plots and filmic structures.